Antiseptic prophylaxis and therapy in ocular infections principles, clinical practice and infection control - Kramer, Axel 1946-; Behrens-Baumann, Wolfgang (Karger, 2002)
This volume collects for the first time interdisciplinary findings in ophthalmology concerning effectiveness and indications of antiseptics for the prophylaxis and therapy of infections.The first part discusses the use of various antiseptics against colonization, contamination and infection of the eye caused by viruses, bacteria, fungus and protozoa in comparison to topical antibiotics. The spectrum of action, the risk of resistance of only microbiostatic active agents and the galenic requirements of antiseptics are included as well as the local and systemic tolerance. New data to iodophors, polyhexanide and magnesium monoperphthalate are presented, and, for the first time, microbiologic requirements of ocular antiseptics are defined. In the second part the current scientific knowledge of prophylaxis and therapeutic antisepsis is presented including Credé's prophylaxis and requirements in cornea banks. The final part is reserved for additional topics such as isolation techniques, hand hygiene, hygiene of contact lenses and microbiological diagnostics.To ophthalmologists, optometrists and opticians this book will give indispensable information on latest clinical and experimental findings in the field. It will also be essential reading to hygienists, microbiologists, infectionists, pharmacologists, pharmacists, and pediatricians interested in ophthalmologic issues
Keywords: Ophthalmology; Infectious Diseases; Microbiology; Preventive Medicine; Augenkrankheit; Antiseptikum; Infektionskrankheit; Auge; Aufsatzsammlung